Ferrocene cocatalysis for ruthenium-catalyzed radical miniemulsion polymerization. (5th December 2016) - Bultz, Elijah; Ouchi, Makoto; Fujimura, Kojiro; Sawamoto, Mitsuo; Cunningham, Michael F.
Abstract: In this study we achieved an efficient metal-catalyzed radical "miniemulsion" polymerization with ferrocene (FeCp2 ) as a cocatalyst in conjunction with a thermoresponsive PEG containing ruthenium catalyst for the polymerization of methacrylate monomers. The iron-cocatalysis worked well even in the miniemulsion similar to homogeneous solution system. The secondary catalytic cycle by ferrocene allows regeneration of Ru(II) activator species through reduction of accumulated Ru(III) deactivator as well as promotion of halogen-capping or deactivation for the active radical species. The effectiveness of this iron cocatalyst in miniemulsion was investigated with both higher polymerization rate and reaching conversion (>90%) than without FeCp2 . In this system, the halogen counterion on the cationic surfactant was a major factor in determining the polymerization rate and the end group fidelity. Interestingly, when a non-ionic surfactant was used for the FeCp2 -cocatalyzed miniemulsion, a simple addition of salt carrying common halogen ion (e.g., NaCl) in aqueous phase was very effective in terms of polymerization control. Graphical abstract: Highlights: Ferrocene works as a cocatalyst for miniemulsion polymerization on the basis of ruthenium-catalyzed living radical polymerization. Addition of ferrocene allowed an acceleration of polymerization while keeping polymerization control. When a nonionic surfactant is used, a combination of NaCl is helpful to improve the polymerization control. Ferrocenium ion (FeCp2 + Cl − ) could survive on the surface with the aid of the common ion source to work as a deactivator for radical species.